Potency and acceptability of oral misoprostol compared with vaginal misoprostol prior to first trimester abortion - Varsha Kotwal (Barpeta Obstetrics and Gynaecological Society, 2020)
Objectives: Present study was done to assess the effectiveness and acceptability of oral misoprostol compared with vaginal misoprostol for cervical priming before termination of first trimester pregnancy. Methodology: One hundred twenty patients who are voluntarily opting for termination of pregnancy were randomly divided into oral misoprostol group and vaginal misoprostol group. The patients were given 400µgm of misoprostol either by oral route or by vaginal administration 4 hours before surgical termination of pregnancy. The data collection was done which was based on questionnaire system, vaginal bleeding and abdominal pain was noted. Results: There was no significant differences in oral and vaginal misoprostol as far as cervical dilatation is concerned (5.63mm versus 5.43mm). The women in vaginal group experienced more bleeding 42% versus 24% in oral group. A total of 89% patients in oral misoprostol group expressed their satisfaction whereas a total number of 75% patients in vaginal misoprostol group were satisfied. Conclusion: The effectiveness of oral misoprostol is similar to vaginal misoprostol for cervical ripening but women are more satisfied in oral misoprostol group than vaginal group.